ZnO thin films implanted with Al, Sb and P: optical, structural and electrical characterization - Viseu, T. M. R. (2009)
In this work we report a study on the structure, optical and electrical properties of P, Sb and Al implanted ZnO thin films that had been produced by r.f. magnetron sputtering. The influence of the different replacing atoms on the structure and properties of the films has been explored. Looking for the best annealing conditions, two different annealing temperatures (300ºC and 500ºC) have been employed. Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), X-ray diffraction, transmittance and d.c conductivity measurements have been used to characterize the samples. X-ray diffraction and Raman scattering patterns confirm that after annealing, doped films keep a polycrystalline nature with (002) preferred orientation. These films remain very transparent and the electrical conductivity increases significantly after the 500ºC annealing, reaching values of 10.9 (cm)-1 in the P-doped, 10.33 (cm)-1 in the Al-doped and 0.56 (cm)-1 in the Sb-doped samples